Domestic violence: who's problem? - Krizsan, Andrea; Paantjens, Marjolein (The Greek Review of Social Research, 2016)
This article juxtaposes shifts in prevailing frames on domestic violence in the Netherlands, Hungary and the EU. Domestic violence, first brought on the political agenda by women’s rights proponents as a problem related to gender inequalities, has been framed and re-framed under the influence of mainstream policy makers. The analysis of these frames shows how shifts in the gender of governance, particularly the marginalization of feminist NGO voices, have led to shifts in the governance of gender. These shifts caused a weakening or even disappearance of gender-equality considerations in domestic violence policies, or an integration of it in a broader framework thereby going beyond gender specific interests. The authors argue that strengthening government engagement on the issue of domestic violence goes hand in hand with a de-gendering in the articulation of the problem. This shift has taken away the privileged position of women’s rights proponents to speak out on the issue, and established the interests of other members of society to speak on it by affirming its cross-societal nature.